2014
DOI: 10.1038/pr.2014.142
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and interpretation of acylcarnitine profiles in dried blood spot and plasma of preterm and full-term newborns

Abstract: Background: Acylcarnitines are biomarkers of fatty acid metabolism, and examining their patterns in preterm newborn may reveal metabolic changes associated with particular conditions related to prematurity. Isomeric acylcarnitines in dried blood spots (DBS) and plasma have never been assessed in preterm infants. Methods: We studied 157 newborn divided into four groups by weeks of gestational age (GA), as follows: 22-27 wk in group 1; 28-31 wk in group 2; 32-36 wk in group 3; and 37-42 wk in group 4. Samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
4
28
1
1
Order By: Relevance
“…While no other published study that we are aware of has used the combination of these markers for gestational dating, our findings are in agreement with other studies that have demonstrated an association between PTB and many of the individual biomarkers studied including those that have found that differences remain after accounting for SGA and feeding status. 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 Like other investigators we observed significant differences between PTBs and term births in free carnitine 33 , 39 ; short-, medium-, and long-chain acylcarnitines 33 , 39 , 40 , 41 , 43 ; amnio acids 39 , 40 , 41 , 43 ; TSH 35 , 37 , 50 ; and 17-OHP. 47 , 51 , 52 Although it is unclear what specifically underlies the differences observed and why they appear useful for gestational dating, it appears that both etiological and maturational underpinnings may exist that are marker specific.…”
Section: Commentsupporting
confidence: 85%
See 1 more Smart Citation
“…While no other published study that we are aware of has used the combination of these markers for gestational dating, our findings are in agreement with other studies that have demonstrated an association between PTB and many of the individual biomarkers studied including those that have found that differences remain after accounting for SGA and feeding status. 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 Like other investigators we observed significant differences between PTBs and term births in free carnitine 33 , 39 ; short-, medium-, and long-chain acylcarnitines 33 , 39 , 40 , 41 , 43 ; amnio acids 39 , 40 , 41 , 43 ; TSH 35 , 37 , 50 ; and 17-OHP. 47 , 51 , 52 Although it is unclear what specifically underlies the differences observed and why they appear useful for gestational dating, it appears that both etiological and maturational underpinnings may exist that are marker specific.…”
Section: Commentsupporting
confidence: 85%
“…While our hypothesis that markers used for newborn screening could also be used for gestational dating purposes is novel, the work is well supported by previous studies demonstrating that many of these routinely collected markers (eg, acylcarnitines, amino acids, thyroid-stimulating hormone [TSH]) are related to PTB and to week of gestation and have heritable components that are robust in small-for-gestational-age (SGA) infants. 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 In the present study, we developed and evaluated a metabolic dating algorithm using a large and diverse sample of California newborns who had ultrasound dating between 11–20 weeks of gestation. We focused specifically on the capacity of markers to differentiate PTBs from term births and to assign a specific gestational age in the preterm group.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the concentrations of AA and AC in these neonates can offer some information about neonatal metabolic or nutritional status is still unknown. As reported previously, AA and AC concentrations varied obviously with birth weight [11]; therefore, VLBW and LBW neonates may have different mean values from NW neonates, and different cutoffs need to be defined to reduce the risks of false-positive cases [12]. Thus, the aim of the present study was to identify the AA and AC profiles in DBS specimens of LBW and VLBW neonates, then compare with NW neonates, and make a contribution to the determination of cutoff values of VLBW and LBW neonates.…”
Section: Introductionsupporting
confidence: 84%
“…The history of patient 3 adds to the discussion whether cut-off ranges in newborn screening may be applied for term and preterm newborns. Whereas previous data suggested that equal cut-offs may be applied [ 40 , 41 ], it recently has been shown that concentrations of acylcarnitines were lower in healthy preterm compared to term newborns [ 42 ]. Many reasons have been postulated, including endogenous and metabolic differences due to lower birth weight and immaturity, and the effect of treatments administered in newborn intensive care units [ 42 ].…”
Section: Discussionmentioning
confidence: 99%